2013
DOI: 10.1002/wow3.37
|View full text |Cite
|
Sign up to set email alerts
|

Role of minimum wages in rebalancing the economy

Abstract: Minimum wages can be a powerful tool for supporting decent work goals and can be a crucial component to the strengthening of social protection floors and poverty alleviation efforts. This paper argues that effectiveness of minimum wages depends on three aspects: first, on the legal coverage of minimum wage systems; second, the level at which minimum wages are set; and third, the ability to ensure compliance with legal minimum wage provisions, so as to ensure the goal of improving incomes and reducing inequalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Before we move on to discussing the impact on household consumption, we note here briefly that the minimum wages help increase earnings/wages and consumption among low-paid workers. There is a vast literature from the developing countries that offer evidence of consumption enhancing and wage inequality dampening effects of the minimum wages (see, e.g., Belser & Rani, 2011;Mansoor & O'Neill, 2020;Rani et al, 2013). Also, many studies have found a negative relationship between poverty and minimum wages (Alaniz et al, 2011;Bird & Manning, 2008;Gindling & Terell, 2010).…”
Section: Upsurge In Minimum Wage Violation In Post-lockdownmentioning
confidence: 99%
“…Before we move on to discussing the impact on household consumption, we note here briefly that the minimum wages help increase earnings/wages and consumption among low-paid workers. There is a vast literature from the developing countries that offer evidence of consumption enhancing and wage inequality dampening effects of the minimum wages (see, e.g., Belser & Rani, 2011;Mansoor & O'Neill, 2020;Rani et al, 2013). Also, many studies have found a negative relationship between poverty and minimum wages (Alaniz et al, 2011;Bird & Manning, 2008;Gindling & Terell, 2010).…”
Section: Upsurge In Minimum Wage Violation In Post-lockdownmentioning
confidence: 99%
“…The advantage of a sectoral minimum is that it can raise the pay of more workers since it can better target low pay in each sector. But sectoral minimum wages can also result in a lack of coverage for large sections of the workforce [12]. In addition, sectoral or occupational rates can add complexity and result in myriad rates for each industry.…”
Section: Variations In Legislated Minimum Wages Across Groups Of Workersmentioning
confidence: 99%
“…There have been numerous and highly contentious debates on the ability of the minimum wage to reduce poverty in the United States (see, for example, Card and Krueger, 1995a;Neumark et al, 1998). In developing countries, the legal minimum wage is sometimes relatively high compared to average wages (Rani et al, 2013a), which could imply that minimum wages have the potential to affect a larger fraction of the population. Yet with large informal sectors and lax enforcement, it is not always the case that minimum wages will affect many in developing country labour markets.…”
Section: Effect Of Minimum Wages On Poverty Income and Distribution mentioning
confidence: 99%